Hardware architecture for perceptual watermarking and data concealment in audio signals - Robertus Wahendro Ali. (2008)
Hiding data is increasingly important for many applications, and is an active research area. In this thesis, we present a technique of hiding data in audio signals and the hardware architecture required for implementation.